The interaction of poetry and politics : read in the Algerian political modern poetr) - Laguane, Ibrahim (Milev Journal of Research and Studies, 2017)
The present study is involved a number of political issues addressed by the Algerian poets in the national movement’s period. They have used their poetry as a way for fighting. In addition , they played a great role in making the Algerian people award of the colonization risk affecting their physical and moral existence through coping with the activity of the association of Muslim Scholars. They also crystallized their national and revolutionary political consciousness responding to the political issues related to the liberation revolution. They talked about the security council, the prosecutors, the political parties, and the Unity of the Arab Maghreb. They also drew the features of the coming political vision for them; and thus, they revived their relationship with their historical Arab and Islamic roots. They strengthened their relationship with the Arab’s central issue (liberation of Palestine).